2016
DOI: 10.1039/c6py01417h
|View full text |Cite
|
Sign up to set email alerts
|

LED and visible light-induced metal free ATRP using reducible dyes in the presence of amines

Abstract: A new photoinitiating system involving electron acceptor dyes, namely, eosin Y and erythrosin B, in conjunction with alkyl halides and amines for photoinduced ATRP of (meth)acrylates and vinyl monomers in the absence of inorganic catalysts is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
110
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 35 publications
2
110
1
9
Order By: Relevance
“…Verschiedene Herangehensweisen wurden vorgeschlagen und erfolgreich eingesetzt, um die Katalysatorkonzentration zu reduzieren, wie die Verwendung von Reduktionsmitteln, [2] die Entwicklung komplexer Katalysatorsysteme [3] und elektrochemische Versuchsanordnungen. [4] Photochemische Methoden einschließlich einer direkten Bestrahlung [5] und des Einsatzes verschiedener Sensibilisatoren, [6] Farbstoffe, [6,7] Nanopartikel [8] und porçser Materialien ergaben eine vielversprechende Reduzierung der Menge an Cu-Katalysatoren, die fürA TRP bençtigt werden. Das System wurde auch fürK lick-Reaktionen mit photochemischer Reduktion von Cu II zu Cu I angepasst.…”
unclassified
“…Verschiedene Herangehensweisen wurden vorgeschlagen und erfolgreich eingesetzt, um die Katalysatorkonzentration zu reduzieren, wie die Verwendung von Reduktionsmitteln, [2] die Entwicklung komplexer Katalysatorsysteme [3] und elektrochemische Versuchsanordnungen. [4] Photochemische Methoden einschließlich einer direkten Bestrahlung [5] und des Einsatzes verschiedener Sensibilisatoren, [6] Farbstoffe, [6,7] Nanopartikel [8] und porçser Materialien ergaben eine vielversprechende Reduzierung der Menge an Cu-Katalysatoren, die fürA TRP bençtigt werden. Das System wurde auch fürK lick-Reaktionen mit photochemischer Reduktion von Cu II zu Cu I angepasst.…”
unclassified
“…Various photoactive compounds, such as photoinitiators, [8] dyes, [9] mesoporous structures, [10] and nanoparticles, [11] have been successfully employed the electron transfer and reduction of Cu II to Cu I , which in turn catalyzes the ATRP process. [14] It was recently demonstrated that the photoinduced ATRP method can also be applied in completely organic systems by using phenothiazines [15] and dyes [16] as photoreductants. [12] Photoinduced electron-transfer-promoted ATRP has also been reported for Ir(ppy) 3 -based systems by Hawker and co-workers.…”
Section: Living Cationic Polymerization Of Vinyl Ethers Through a Phomentioning
confidence: 99%
“…Poly(vinyl ether) chains are then grown through successive photoinduced radical oxidation/addition/deactivation (PROAD) in a controlled manner. [14] It was recently demonstrated that the photoinduced ATRP method can also be applied in completely organic systems by using phenothiazines [15] and dyes [16] as photoreductants. [4] In recent years, there has been tremendous interest in developing new controlled/living polymerization (CLP) methods, involving almost all modes of polymerization processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy involves the application of conventional Type II photoinitiators and certain dyes in conjunction with amines as electron sources and alkyl halides as initiators [33][34][35]. In this particular case, the mechanism of radical formation occurs by a reductive quenching mechanism.…”
Section: Introductionmentioning
confidence: 99%